1996
DOI: 10.1007/bf01279653
|View full text |Cite
|
Sign up to set email alerts
|

Shape optimization of interior cutouts in composite panels

Abstract: This paper presents validated results of the optimization of cutouts in laminated carbon-fibre composite panels by adapting a recently developed optimization procedure known as Evolutionary Structural Optimization (ESO). An initial small cutout was introduced into each finite element model and elements were removed from around this cutout based on a predefined rejection criterion. In the examples presented, the limiting ply within each plate element around the cutout was determined based on the Tsai-Hill failu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Studies were also performed in finding optimised cutout shape, e.g. Falzon et al [5] showed that for a quasi-isotropic panel under in-plane shear load the optimum cutout shape was a diamond rather than the conventional circular. From the results of Kumar and Singh [6], quasi-isotropic laminate under combined in-plane loads with elliptical vertical cutout has the maximum buckling load and post-buckling strengths, whereas the laminate with elliptical-horizontal cutout has the minimum strengths.…”
Section: Introductionmentioning
confidence: 99%
“…Studies were also performed in finding optimised cutout shape, e.g. Falzon et al [5] showed that for a quasi-isotropic panel under in-plane shear load the optimum cutout shape was a diamond rather than the conventional circular. From the results of Kumar and Singh [6], quasi-isotropic laminate under combined in-plane loads with elliptical vertical cutout has the maximum buckling load and post-buckling strengths, whereas the laminate with elliptical-horizontal cutout has the minimum strengths.…”
Section: Introductionmentioning
confidence: 99%
“…116 In composite optimization studies, usually the material system or dimensions (size) were optimized. In some studies, shape 55,72,183,190,200,241,242,289,313,354,383,547 774,776,806,826,828,846,860,882,886,888,894,925,939,966,968,976,982 of the structure was optimized. In a few studies, concurrent optimization was performed, in which the design of the part as well as its manufacturing process were optimized.…”
Section: Introductionmentioning
confidence: 99%
“…In composite optimization studies, usually the material system or dimensions (size) were optimized. In some studies, shape 55,72,183,190,200,241,242,289,313,354,383,547,588,619,668670,675,683,707,733,742,779,800,810,829,855,875,916,1000,1003 or topology 149,219,243,247,291,325,348,358,378,427,446,447,463,466,472,490,503,514,528,547,582,596,607,651,688,730,732,744,774,776,806,826,828…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One way of reducing stress concentration without adding structural weight is to find the optimum cutout shape. Falzon et al [7] used the Evolutionary Structural Optimisation (ESO) method to optimise cutout shapes in a square composite panel under different types of loading. They found that under shear load, the optimum cutout shape for a quasi-isotropic laminate was a rectangle of aspect ratio 1.86 and orientated 45° to the horizontal axis.…”
Section: Introductionmentioning
confidence: 99%